Standardization of different pre-sowing seed treatments of selected botanicals on growth, yield and yield attributing traits of Okra (Abelmoschus esculentus) variety angel - Cheruku Anand Jaya Suriya; Prashant Kumar Rai; Vaidurya Pratap Sahi; Bazil Avinash Singh (Annals of Agricultural Research, 2024)
The study conducted during the Rabi season of 2022-2023 at the Field Experimentation centre, Department of Genetics and Plant Breeding, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, Uttar Pradesh, aimed to determine the impact of pre-sowing seed treatments of selected botanicals on the growth, yield, and yield attributing traits of Okra (Abelmoschus esculentus) Var: Angel. The experiment was design reducing a Randomized Block Design (RBD) with twelve different treatments and 3 replications. In this study, Okra seeds were subject to various treatments, including T0- Untreated, T1-Pongamia leaf powder @ 50gms, T3-Pongamia leaf powder @ 100 gms, T4-Pongamia leaf powder @150gms, T5-Prosopis leaf powder @ 50 gms, T6-Prosopis leaf powder @100 gms, T7-Prosopis leaf powder @150gms, T8-Arjuna leaf extract @ 3% for 12hrs, T9-Arjuna leaf extract @ 5% for 12 hrs, T10-Arjuna leaf extract @ 6% for 12 hrs, T11-Baheda leaf extract@ 3% for 12 hrs and T12-Baheda leaf extract @ 5% for 12 hrs. Among these treatments, there suits indicated that the treatment labeled as T3, involving the use of Pongamia leaf powder (150grams), yielded the most favourable out comes in terms of growth and yield parameters. In contrast, the control group (T0) showed the least promising results. This research provides valuable insights into the potential benefits of using Pongamia leaf powder as a pre-sowing seed treatment for Okra cultivation during the Rabi season, which may contribute to improved growth and yield in this crop.